2008
DOI: 10.1007/s00198-008-0698-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with teriparatide in postmenopausal osteoporosis; impact of a patient education and follow-up program: the French experience

Abstract: Postmenopausal osteoporotic women treated by teriparatide and enrolled in an education and follow-up program have a high persistence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 19 publications
6
29
0
1
Order By: Relevance
“…Persistence data were particularly high (especially for daily drug treatment) as well as satisfaction with the program. These results were in line with similar programs for teriparatide conducted in France and the UK 9,10 . However, when broadening this issue of adherence to osteoporosis drugs to all available studies, the efficacy of patient education is much more controversial.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S supporting
confidence: 90%
“…Persistence data were particularly high (especially for daily drug treatment) as well as satisfaction with the program. These results were in line with similar programs for teriparatide conducted in France and the UK 9,10 . However, when broadening this issue of adherence to osteoporosis drugs to all available studies, the efficacy of patient education is much more controversial.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S supporting
confidence: 90%
“…After first visit when therapy was prescribed, all our patients were met or contacted after 1 and 3 months (to control biochemical serum parameters, including potential calcium fluctuation) and visited again after six and 12 months to accomplish to the National health care prescription protocol. Training on self-administered subcutaneous injection (patients and/or their relatives), motivation instilled in the patients, subsequent visits to the first meeting set, possibility of contact by telephone (for potential presence of any problems or side effects), monitoring of blood test during the first months, when is higher the risk of treatment dropout, were all likely reasons which justify the high persistence and adherence to Teriparatide in our study as compared to others evaluating the same molecule (35)(36). Adverse events were few and modest; the self-administered subcutaneous injection of TPTD resulted easy for patients.…”
Section: Discussionmentioning
confidence: 75%
“…In particular the adherence to TPTD during the first semester treatment has allowed patients to obtain improvement of quality of life, and a strong stimulus for TPTD treatment persistence and adherence. Other studies have been performed in different countries (34)(35)(36)(37)(38) to examine persistence and adherence to the same treatment have found high persistence to the therapy but with lower rate (81%) after 18 months (35) while others have published data only at 12 months (37). A limitation of our study could be found in the fact that our patients suffered from severe osteoporosis and have previously sustained several fragility fractures, which had significantly impaired the quality of life and undoubtedly accentuated their awareness of the seriousness of the disease and willingness to continue the pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(90) Similar results were seen in a French study looking at persistence in postmenopausal patients enrolled in an education and follow-up program and found that 81.5% were still on treatment at 15 months. (91) Recently, Black and colleagues (92) have shown that those who comply with therapy of PTH show better densitometric results.…”
Section: Safety In Hypoparathyroidism Trialsmentioning
confidence: 99%